2003
DOI: 10.1021/es020978r
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Dechlorination of Carbon Tetrachloride and Tetrachloroethylene by Zerovalent Silicon−Iron Reductants

Abstract: Reductive dechlorination of carbon tetrachloride (CT) and tetrachloroethylene (PCE) by zerovalent silicon (ZVS, Si0) and the combination of Si0 with metal iron (Fe0) was investigated as potential reductants for chlorinated hydrocarbons. The X-ray photoelectron spectroscopy (XPS) was used to identify the surface characteristics of Si0. CT and PCE can be completely degraded via sequential reductive dechlorination to form lesser chlorinated homologues by Si0. Productions of chloroform (CF) and trichloroethylene (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 36 publications
0
62
1
Order By: Relevance
“…Based on the measurement of CT and its products, the total carbon mass balance was about 50% at the end of reaction. Many studies have reported that CT was mainly transformed to CF through hydrogenolysis pathway by iron-bearing soil minerals and that the extent of CF production was dependent on the type of soil minerals [20][21][22][23]. In the experimental results reported by Zwank et al, the portions of CF formation during the reductive dechlorination of 10 M CT by mackinawite, goethite, magnetite, lepidocrocite, hematite, and siderite were 55%, 33%, 80%, 14%, 17%, and 33%, respectively [23].…”
Section: Treatment Of Kinetic Datamentioning
confidence: 99%
“…Based on the measurement of CT and its products, the total carbon mass balance was about 50% at the end of reaction. Many studies have reported that CT was mainly transformed to CF through hydrogenolysis pathway by iron-bearing soil minerals and that the extent of CF production was dependent on the type of soil minerals [20][21][22][23]. In the experimental results reported by Zwank et al, the portions of CF formation during the reductive dechlorination of 10 M CT by mackinawite, goethite, magnetite, lepidocrocite, hematite, and siderite were 55%, 33%, 80%, 14%, 17%, and 33%, respectively [23].…”
Section: Treatment Of Kinetic Datamentioning
confidence: 99%
“…Most of the CPs are listed as priority pollutants by the USEPA (Cheng et al, 2007;Ma et al, 2014). Reductive dechlorination is an effective method to detoxify these contaminants and has been widely investigated Doong et al, 2003;Yan et al, 2010;Xu and Gao, 2007;Zhu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, double-metal-catalyzed dechlorination materials have been developed, which greatly improve the dechlorination efficiency, and have been used to remediate water and soil contaminated by chlorinated pollutants, such as chlorinated hydrocarbons, chlorophenols, chlorobenzenes, polychlorinated biphenyls and other polychlorinated aromatics (Jovanovic et al, 2015;Liu et al, 2014;Wei et al, 2014;Yang et al, 2014). In these bimetallic materials, Fe, as a metal with low standard redox potential, is an electron donor and hydrogen donor to reduce the chlorinated organic compounds (Doong et al, 2003;Zhu et al, 2010), while the second metal (Ni, Pd, Cu, or Ag) with high standard redox potential, promotes the reactivity via hydrogenation and accelerating corrosion (DeVor et al, 2008;Nie et al, 2013;Wei et al, 2006;Zhang et al, 2009;Zhu et al, 2010), acting as a catalyst and accelerator. Among these materials, Pd/Fe has attracted a great deal of attention thanks to the low cost of Fe and excellent hydrogenation activity of Pd (Wei et al, 2006;Yan et al, 2010), but the cost of Pd greatly restricts the wide application of Pd/Fe catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…One of main mechanisms to treat CAHs under anaerobic environment is a reductive dechlorination. Reductive dechlorination of various CAHs such as tetrachloroethylene (PCE), trichloroethylene (TCE), 1,1,1-trichloroethane (1,1,1-TCA) and carbon tetrachloride (CT) can be achieved by various natural or synthesized reductants including zero-valent iron [2][3][4], ferrous iron [5], iron-oxides (e.g. goethite, hematite and magnetite) [6][7][8][9][10][11][12][13][14], iron hydroxides (green rust) [15][16][17][18], iron sulfide (FeS) [19][20][21], pyrite (FeS 2 ) [9,22] and iron-phyllosilicates [23].…”
Section: Introductionmentioning
confidence: 99%